Penggunaan Paraban Positif-Negatif dan Fungsinya (Kajian Etnolinguistik) - Hermintoyo Hermintoyo (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2021)
The use of language in informal communication tends to be a variety of familiar, relaxed. There is closeness between the wearers, one of which is the use of the greeting word Paraban. The salutation word paraban is an additional attribute given to the real name. Paraban is etymologically given conventionally by looking at physical, habit, pleasure, social status, and behavior. There are negative and positive greetings from this paraban. In the context of use it is carried out in intimate communication, and in free situations, such as playing, meeting or in certain events. This context serves a function as: identity, address, social status, and seduction. Psychological use of paraban is generally considered normal for its owner, except for negative paraban. Paraban felt negative because he mentioned physical disabilities, behavior, the profession concerned. Even though it feels painful, the person concerned cannot refuse it even because the habit of daily paraban calls has become commonplace. However, the negative paraban call must be made from close friends, playmates if it is not a close friend or younger age then the person concerned will be offended and angry.